Multi-proxy record of orbital-scale changes in climate and sedimentation during the Weissert Event in the Valanginian Bersek Marl Formation (Gerecse Mts., Hungary). (July 2017) - Bajnai, Dávid; Pálfy, József; Martinez, Mathieu; Price, Gregory D.; Nyerges, Anita; Főzy, István
Abstract: The Valanginian positive carbon isotope excursion and associated environmental changes, known as the Weissert Event, is the first in the series of Cretaceous Earth system perturbations. Here, we develop a multiproxy cyclostratigraphy from a 31.2-m-thick Upper Valanginian to lowermost Hauterivian section of the Bersek Marl Formation in Gerecse Mountains, Hungary, comprising alternating marlstone layers of varying clay and carbonate content. The bulk carbonate δ 13 C signal shows sustained, elevated values (up to 2.7‰) up to 19.2 m, followed by a decreasing trend upsection. Together with biostratigraphic data, this suggests that the lower part of the section was deposited during the plateau phase of the Late Valanginian Weissert Event. Spectral analyses of the multiproxy dataset, including magnetic susceptibility measurements and gamma-ray spectroscopy on the lower part of the section, led to the identification of precession, obliquity, and long and short eccentricity signals. A mean sedimentation rate of 14 m/Myr was calculated based on astronomical tuning. The cyclicity in the proxy signals reflects dilution cycles induced by the fluctuating rate of detrital runoff into the basin. This supports the idea that orbitally-forced humid-arid cycles controlled the pelagic alternating sedimentation during the Early Cretaceous throughout the Tethyan area. Highlights: Magnetic susceptibility, gamma ray, δ 13 C, and δ 18 O data from the Bersek Formation. A new western Tethyan record of the Late Valanginian Weissert Event is described. Spectral analysis reveals presence of Milankovitch periodicities in proxy signals. Dilution cycles control the sedimentation and the proxy signals. Minimum duration of the δ 13 C plateau of the Weissert Event is 1.25 Myr long.